The Consuming Temple : Jews, Department Stores, and the Consumer Revolution in Germany, 1880-1940 - Lerner, Paul Frederick (Book collections on Project MUSE., 2015)
Department stores in Germany, like their predecessors in France, Britain, and the United States, generated great excitement when they appeared at the end of the nineteenth century. Their sumptuous displays, abundant products, architectural innovations, and prodigious scale inspired widespread fascination and even awe; at the same time, however, many Germans also greeted the rise of the department store with considerable unease. This book explores the complex German reaction to department stores and the widespread belief that they posed hidden dangers both to the individuals, especially women, who frequented them and to the nation as a whole.